The effects of individual-level and area-level socioeconomic status on preferences and behaviour in leisure time physical activities: a cross-sectional analysis of Chinese adults. Issue 4 (2nd October 2022) - Chen, Nan; Lee, Kangjae Jerry; Kim, Jaehyun; Tsai, Chiung-Tzu Lucetta
ABSTRACT: This study examines the extent to which individual and area-level socioeconomic statuses (SES) correlate with the preferences and participation in physical activities during leisure time. A multistage, random clustered sample taken from the China Health and Nutrition Survey of 2015 was used. Results from multi-level analyses indicated that both individual income and area-level SES were significantly associated with participation in walking, whereas individual educational attainment was positively associated with participation in sports. Moreover, leisure preference mediated the relationship between individual SES, area-level SES, and participation in sports. Based on these findings, this article suggests that both individual and area-level influences should be taken into account when developing health policies to promote active lifestyles. In addition, mediation effect of leisure preference in LTPA should be emphasized when implementing intervention program.